History of Zionism, 1600-1918, Vol. 1 (of 2) - Sokolow, Nahum, 1859-1936; Balfour, Arthur James, 1848-1930; Bryce, James Bryce, Viscount, 1838-1922; Sykes, Mark, 1879-1919; Solomons, Israel, 1860-1923 (Salt Lake City, UT : Project Gutenberg, 2023)
"History of Zionism, 1600-1918, Vol. 1 (of 2)" by Nahum Sokolow is a historical account written in the early 20th century. The work delves into the origin and development of Zionism, particularly focusing on its evolution within England and France, exploring the diverse aspirations and sentiments related to the Zionist idea over several centuries. This book is aimed at readers interested in understanding the historical context of Zionism and its multifaceted influences. The opening of the volume presents the author's intent to investigate the largely unexplored historical narrative of Zionism from its inception to 1918. Sokolow articulates how his exploration goes beyond just the contemporary movements associated with Zionism, emphasizing the importance of historical, political, and religious factors that have shaped public opinion in England and the sentiments of Jewish communities. The introduction sets the groundwork for a detailed examination of the ideological currents in Zionism, revealing several historical instances and figures that have contributed to its development, while aiming to illuminate its significance within the broader context of the Jewish national revival. (This is an automatically generated summary.)
Release date is 2023-05-26
Richard Hulse, Tony Browne, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Jews -- Restoration; Zionism -- History